Legalitas Cryptocurrency: Tinjauan terhadap Fatwa-Fatwa Institusi dan Personal - Arzam, Arzam; Fauzi, Muhammad; Mursal, Mursal; Muid, Abdul (Al-Muzdahir : Jurnal Ekonomi Syariah, 2023)
This study aims to review and comprehensively explain the legality of Cryptocurrency based on a number of institutional and personal fatawa. To answer the research objectives, it was carried out using descriptive research with a qualitative approach. The research data comes from secondary data in the form of institutional and personal fatawa that have been published online, and are accompanied by supporting writings explaining these fatawa. The collected research data were analyzed by following the steps including material collection, discussion, and descriptive analysis. This research shows that a number of institutional and personal fatawa are divided into three decisions on the legality of Cryptocurrency, namely the first is Halal Cryptocurrency; on the grounds that it can be treated as a form of Maal (property), because it is based on social approval and general use so it is permissible to own;, trade;, transact;, etc. there is a clear decision), on the grounds of excessive gharar (speculation); security risk; can easily be used in illegal activities;. Third, Cryptocurrencies are illegal, for various reasons, they are not currency and are not legal means of payment; decentralized validation; excessive gharar (speculation); can easily be used for maysir (gambling);, and used to fund terrorists;. This research needs to be continued considering the limitations it has, such as seeing arguments against Cryptocurrency due to its properties (characteristics) so it is very good and it takes hard work to see it from various perspectives.